Der Schutz materieller Kulturgüter in Lateinamerika - universelles, regionales und nationales Recht - Ochoa Jiménez, Maria Julia (Universitätsverlag Göttingen, 2011)
The main reason why Latin America is a cultural diverse region is because of the indigenous peoples who inhabit it. That is why indigenous peoples' interests on their cultural property have to be taken into account when this matter is to be legally regulated in Latin American countries. In order to ascertain whether that has occurred, the book explores relevant legal instruments at the international and regional levels and compares national norms in some Latin American countries, particularly those concerning ownership. It concludes that recognition of indigenous interests in Latin American law on cultural property is still a pending task.